A Kim Jong-Il production : the extraordinary true story of a kidnapped filmmaker, his star actress, and a young dictator's rise to power /: the extraordinary true story of a kidnapped filmmaker, his star actress, and a young dictator's rise to power. (2015) - Unknown
No abstract available